The Possibility and Limits of the Experiential Knowledge of God in Islamic Thought with an Emphasis on the Sadrian Point of View - Ali Shirwani Shirwani (حکمت اسرا, 2011)
Many of the prominent Christian philosophers of religion interpret religious experience as experience with the Divine. According to individuals such as Swinburne and Alston—two leading contemporary philosophers of religions—experience with the Divine is a type of experiential knowledge of God. By presenting the viewpoint of Sadrian Transcendental Theosophy regarding the limits and types of man’s knowledge of God, this article paves the way for understanding MullÁSadrÁ’s stance regarding experiential knowledge as it pertains to God and elucidates on its relevant principles. By way of example, one of these principles is the following: on no account can the core of God’s essence be disclosed to anyone except God Himself. Hence, experiential knowledge of God will never pertain to the core of His essence. However, experiential and unmediated knowledge of God’s Names and manifestations is a possible phenomenon that cannot only be materialized, but it is actually prevalent. That which is exclusive is knowledge of such a knowledge, not its principles. The levels of this knowledge correspond to the levels of divine proximity. If experiential knowledge of God is an example of knowledge by presence then it will possess one of the highest degrees of gnostic authenticity.